Development of Website-Based Blood Group Database in Pangauban Village, Katapang District, Bandung Regency Sector 7 - Maulani, Nishfi Rahmah; Rahman Alfarisi, Rendi; Ambiya, Utari Nur; Nurkamilah, Milah; Sasyari, Usman; Pratiwi, Anggia Suci; Hendrawan, Budi; Saleh, Yopa Taufik (AbdimasMu UMTAS, 2024)
Database is a collection of files / tables / archives that are interconnected which are stored in electronic storage media. Database creation is the process of creating a design that will support the company's operations and goals. The use of databases in the medical field makes it possible to store data or perform and display data back quickly and easily. In the implementation of this activity, the method used in this community service is counseling and blood group examination using the slide method. A person's blood type is not just a personal identity, some people don't care about their blood type. Some don't even know what their own blood group is. Because we do a blood group check so that we know the blood group of each.